Ab Initio Pseudopotential Study of Cluster Growth of Coinage Metal Telluride Clusters $Au_nTe_m$ (Journal of Atomic and Molecular Sciences, 2010)
The geometries of the lowest-lying isomers of small $Au_nTe_m$ $(n, m=1, 2)$ clusters are determined through the MP2 method. The aspect of gold-telluride interaction, the electron correlation and relativistic effects on geometry, and cluster growth are investigated at the MP2 and CCSD(T) theoretical levels. The results show that the gold-telluride interaction is strong enough to modify the known pattern of bare gold clusters. The electron correlation and relativistic effects are responsible not only for gold-gold attraction but also for additional gold-telluride interaction. Both electron correlation and relativistic effects are essential for determining the geometry and cluster growth of coinage metal telluride compound clusters $Au_nTe_m$.
Keywords: clusters $Au_nTe_m$; electron correlation; relativistic effect.